2016
DOI: 10.1177/1076029616648407
|View full text |Cite
|
Sign up to set email alerts
|

Increased Level of Thrombotic Biomarkers in Patients with Atrial Fibrillation Despite Traditional and New Anticoagulant Therapy

Abstract: The aim of this study was to examine the effect of the traditional oral anticoagulant, warfarin (W), and new anticoagulants, apixaban (A) and rivaroxaban (R), on the level of thrombotic biomarkers in patients with atrial fibrillation (AF). Circulating plasma levels of von Willebrand factor (vWF), prothrombin fragment 1.2 (F1.2), microparticle tissue factor (MP-TF), and plasminogen activator inhibitor (PAI-1) were analyzed as potential markers of clot formation in 30 patients with AF prior to ablation surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…On one hand, it was suggested that the high shear stress associated with severe MR might decrease von Willebrand factor activity 14. On the other hand, concomitant AF complicates the picture, since it is associated with increased von Willebrand factor, even in patients on vitamin K antagonists, rivaroxaban or apixaban 15. We observed a modestly lower rate of major bleeding in patients with MR compared with those with no VHD.…”
Section: Discussionmentioning
confidence: 56%
“…On one hand, it was suggested that the high shear stress associated with severe MR might decrease von Willebrand factor activity 14. On the other hand, concomitant AF complicates the picture, since it is associated with increased von Willebrand factor, even in patients on vitamin K antagonists, rivaroxaban or apixaban 15. We observed a modestly lower rate of major bleeding in patients with MR compared with those with no VHD.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies by Liles et al have examined the use and effects of antithrombotic drugs in patient with AF and shown the drugs’ effects in downregulating the levels of various thrombotic biomarkers. 18 These results, when compared and combined with the current data from this study, may yield important information that will have clinical implications in both the diagnosis and treatment of AF.…”
Section: Discussionmentioning
confidence: 67%
“…17 This elevated inflammatory state has been implicated in both the progression of AF and the increased risk of thrombotic events in these patients. 18…”
Section: Discussionmentioning
confidence: 99%
“…41 The addition of vWF plasma levels to the clinical risk stratification data has shown an independent association between high levels of vWF and the risk of a vascular event. 8,22 CHADS 2 score does not include many common stroke risk factors. Given the need to be more inclusive of common stroke risk factors, many studies have confirmed the ability of CHA 2 DS 2 -VASc to identify "low-risk" patients.…”
Section: Discussionmentioning
confidence: 99%